2015
DOI: 10.1371/journal.pone.0137134
|View full text |Cite|
|
Sign up to set email alerts
|

Transgenic Citrus Expressing an Arabidopsis NPR1 Gene Exhibit Enhanced Resistance against Huanglongbing (HLB; Citrus Greening)

Abstract: Commercial sweet orange cultivars lack resistance to Huanglongbing (HLB), a serious phloem limited bacterial disease that is usually fatal. In order to develop sustained disease resistance to HLB, transgenic sweet orange cultivars ‘Hamlin’ and ‘Valencia’ expressing an Arabidopsis thaliana NPR1 gene under the control of a constitutive CaMV 35S promoter or a phloem specific Arabidopsis SUC2 (AtSUC2) promoter were produced. Overexpression of AtNPR1 resulted in trees with normal phenotypes that exhibited enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(121 citation statements)
references
References 62 publications
8
109
0
4
Order By: Relevance
“…Similar limitations were observed in the AtNPR1 transformants against Verticillium wilt, where protection was observed only against the non-defoliating isolates of V. dahliae and not the defoliating isolates (Parkhi et al 2010b). Nevertheless, there are a large number of reports that show that NPR1 overexpression confers a strong protection against a variety of diseases (Lin et al 2004;Makandar et al 2006;Malnoy et al 2007;Wally et al 2009;Zhang et al 2010;Dutt et al 2015;Silva et al 2015). Thus, controlled expression of NPR1 gene may still prove to be a useful means to confer tolerance to some pathogens in the field.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Similar limitations were observed in the AtNPR1 transformants against Verticillium wilt, where protection was observed only against the non-defoliating isolates of V. dahliae and not the defoliating isolates (Parkhi et al 2010b). Nevertheless, there are a large number of reports that show that NPR1 overexpression confers a strong protection against a variety of diseases (Lin et al 2004;Makandar et al 2006;Malnoy et al 2007;Wally et al 2009;Zhang et al 2010;Dutt et al 2015;Silva et al 2015). Thus, controlled expression of NPR1 gene may still prove to be a useful means to confer tolerance to some pathogens in the field.…”
Section: Discussionmentioning
confidence: 58%
“…Citri (Xcc). A recent study showed enhanced resistance against Huanglongbing disease in citrus plants expressing the AtNPR1 gene (Dutt et al 2015). In our earlier investigations, we found that expression of AtNPR1 in cotton conferred protection against two necrotrophic fungal pathogens, R. solani, (a cause of seedling damping-off) and A. alternata (a cause of foliar disease), two wilt diseases, Fusarium wilt caused by Fov and Verticillium wilt caused by nondefoliating pathotype of Verticillium dahliae, black root rot caused by T. basicola, and reniform nematodes (Parkhi et al 2010a;Parkhi et al 2010b;Kumar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such defenses include generation of reactive oxygen species, callose deposition, synthesis of pathogenesis-related (PR) proteins, and increased activation of systemic acquired resistance (SAR) [23,61]. As with the previously described strategies, this strategy takes advantage of the plant's own natural immune system and does not introduce new metabolic pathways.…”
Section: Upregulating Defense Pathwaysmentioning
confidence: 99%
“…As with the previously described strategies, this strategy takes advantage of the plant's own natural immune system and does not introduce new metabolic pathways. This approach has been successful against bacterial pathogens attacking several host species [62][63][64], and it offers promising results for enhancing resistance to citrus greening [23], a disease of urgency for the citrus industry. Upregulation of defense pathways was also successful against destructive fungal pathogens, including Rhizoctonia solani (the cause of many diseases) and Magnaporthe oryzae (the cause of rice blast) [61,65].…”
Section: Upregulating Defense Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation